A PVC / SBS modified material and preparation method thereof
By adding special plasticizers and other additives to the PVC/SBS modified materials and modifying them through reactions such as esterification, the shortcomings of PVC materials in terms of toughness, impact resistance and stability are solved, and the material performance is significantly improved.
Patent Information
- Application Number
- CN202411825821.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing PVC cable materials have shortcomings in toughness and impact resistance, and the stability of polyvinyl chloride to light and heat is poor, which is easy to decompose and produce hydrogen chloride, resulting in a decline in material performance.
PVC/SBS modified materials are used to prepare plasticizers through esterification, epoxidation and acetylation reactions by blending PVC with SBS and adding special plasticizers, flame retardants, anti-aging agents, stabilizers and lubricants to improve the mechanical properties and stability of the material.
It significantly improves the toughness, impact resistance and comprehensive mechanical properties of PVC materials, while delaying the decomposition process of the material and improving the stability to light and heat.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a PVC / SBS modified material and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is a high molecular polymer that is a white amorphous powder at room temperature. It is synthesized from vinyl chloride monomers through polymerization reactions. PVC is widely used in building materials, films, pipes, and coatings. SBS is a triblock copolymer with styrene and butadiene as monomers. Since SBS has both hard polystyrene segments and soft polybutadiene segments, it has two glass transition temperatures of 100°C at high temperature and -80°C at low temperature, so it has both plasticity and elasticity. Blending SBS with PVC can significantly improve the low-temperature performance and impact strength of the product. However, polyvinyl chloride has poor light and heat stability. It will decompose at temperatures above 100°C or after long-term exposure to sunlight to produce hydrogen chloride, and further autocatalytically decompose, causing discoloration, and the physical and mechanical properties will also decrease rapidly. The use of plasticizers can not only regulate the performance of PVC and expand its scope of use, but also reduce the processing temperature of PVC, shorten the processing time, and reduce the possibility of its decomposition. However, with the restrictions on phthalate plasticizers in Europe and the United States and other countries, the development of new plasticizer substitutes has become a research hotspot.
[0003] A Chinese invention patent with publication number CN109265866A discloses a PVC cable material resistant to pigment migration. The PVC cable material comprises the following components by weight: 100 parts of PVC resin, 5-15 parts of silicone-modified SBS, 25-40 parts of dioctyl azelate, 20-35 parts of titanate-modified white carbon black, 0.5-2 parts of ultraviolet absorber, 5-15 parts of nano titanium dioxide, 3-8 parts of dye and 1-3 parts of antioxidant. The PVC cable material obtained by the invention has good resistance to pigment migration, but its toughness, impact resistance and other properties are poor. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a PVC / SBS modified material and a preparation method thereof.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions:
[0006] A PVC / SBS modified material comprises the following raw materials in parts by weight:
[0007] PVC: 80-100 copies,
[0008] SBS: 20-40 copies,
[0009] Plasticizer: 3-30 parts,
[0010] Flame retardant: 2-4 parts,
[0011] Anti-aging agent: 5-8 parts,
[0012] Stabilizer: 2-3 parts,
[0013] Lubricant: 3-5 parts;
[0014] The plasticizer is prepared by the following method:
[0015] S1: Deionized water, hexamethylenetetramine, tromethamine, and glacial acetic acid are added to the reactor in sequence, stirred, heated to 65-75°C, reacted for 1-2 hours, cooled to room temperature, separated, the water layer removed, and washed with deionized water for 3 times to obtain a first-generation polymer. The reaction equation is shown as follows:
[0016]
[0017] S2: Under nitrogen protection, DMF, first-generation polymer, and anacardic acid were added to the reactor, stirred, and heated to 120-130°C. Then p-toluenesulfonic acid was added, and refluxed for 4-6 hours. After cooling to room temperature, saturated NaHCO 3 The solution was distilled under reduced pressure and dried under vacuum to obtain intermediate 1, and the reaction equation is as follows:
[0018]
[0019] S3: DMSO, intermediate 1, acetic anhydride and p-toluenesulfonic acid are added to the reactor in sequence, stirred, heated to 130-150°C, reacted for 6-8h, and post-treated to obtain intermediate 2, the reaction equation of which is shown as follows:
[0020]
[0021] S4: DMF, intermediate 2 and strong acid cation exchange resin were added to the reactor, stirred, and heated to 60-80°C; then formic acid and 30wt% H 2 O 2 Mix well and slowly add formic acid and H 2 O 2 The mixed solution was added and reacted for 6-8 hours after the addition to obtain intermediate 3, the reaction equation of which is shown as follows:
[0022]
[0023] S5: Add tetrahydrofuran, intermediate 3, acetic anhydride, and strong acid cation exchange resin into a reactor, stir, heat to 120-140°C, react for 6-8h, and post-treat to obtain a plasticizer. The reaction equation is as follows:
[0024]
[0025] Wherein, m is a natural number;
[0026]
[0027] In the step S1, the mass ratio of deionized water, hexamethylenetetramine, tromethamine and glacial acetic acid is 10:2.5:(1.0-1.2):(0.8-1.0).
[0028] In the step S2, the mass ratio of DMF, first-generation polymer, anacardic acid and p-toluenesulfonic acid is 50:(5-10):(15-25):(0.2-0.5).
[0029] In the step S3, the mass ratio of DMSO, intermediate 1 and acetic anhydride is 50:(6-8):(15-20).
[0030] In the step S4, the feed mass ratio of DMF, intermediate 2, formic acid and strong acid cation exchange resin is 50:(5-8):(12-16):(0.5-1).
[0031] In the step S5, the mass ratio of tetrahydrofuran, intermediate 3 and acetic anhydride is 100:(5-10):(20-35).
[0032] The flame retardant is one of tributyl phosphate, tri(2-ethylhexyl) phosphate, and tri(2-chloroethyl) phosphate; the antioxidant is one of N-phenyl-α-aniline, N-phenyl-β-naphthylamine, and N-phenyl-N'-isopropyl-p-phenylenediamine.
[0033] The stabilizer is a combination of one or more of JX-181 organic tin heat stabilizer, JX-107 reverse ester tin heat stabilizer, and JT-101 antimony mercaptan heat stabilizer.
[0034] The lubricant is stearic acid.
[0035] A method for preparing a PVC / SBS modified material comprises the following steps:
[0036] S1: weigh by weight: PVC: 80-100 parts, SBS: 20-40 parts, plasticizer: 3-30 parts, flame retardant: 2-4 parts, antioxidant: 5-8 parts, stabilizer: 2-3 parts, lubricant: 3-5 parts;
[0037] S2: Add all components into a high-speed mixer and mix them. Then, introduce the mixture into a twin-screw extruder for extrusion and granulation, and air-cool and sieve to obtain the PVC / SBS modified material.
[0038] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:
[0039] The invention adopts the reaction of hexamethylenetetramine and tromethamine to prepare a first-generation polymer, and then performs modification through esterification, epoxidation and acetylation reactions to finally prepare an environmentally friendly plasticizer.
[0040] The plasticizer prepared by the present invention introduces a benzene ring structure and an acetyl group into the molecular structure through esterification reaction, epoxidation and acetyl ring-opening reaction, so that the prepared plasticizer itself has a large volume. After the plasticizer is added into the PVC material, the plasticizer separates the PVC molecules and combines with the polar parts on the PVC molecular chain, thereby increasing the free volume inside the polymer, and the moving space between the PVC molecular chains is also increased, and the corresponding ductility of the PVC material is improved, thereby increasing the overall toughness of the polymer, and at the same time, the tensile strength of the polyvinyl chloride molecules can be taken into account, so that the obtained modified material has excellent comprehensive mechanical properties. DETAILED DESCRIPTION
[0041] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.
[0042] Example 1 Preparation of Anacardic Acid:
[0043] Add 600 mL of 95 wt% methanol aqueous solution and 100 g of cashew nut shell liquid to the reactor, stir, and slowly add 50 g of Ca(OH) 2 , react at 50℃ for 3h. After the reaction is completed, filter out the precipitated calcium anacardate, add 200mL methanol to wash, and vacuum dry at 50℃ for 2h to obtain 110g of dry calcium anacardate. Then disperse 110g of calcium anacardate in 440mL of distilled water, add 60mL of 11mol / LHCl and stir for 1h. Then add 300ml of ethyl acetate to extract, wash with 200ml of distilled water, distill the organic phase under reduced pressure at 50℃ for 2h, and dry with 300g of anhydrous sodium sulfate for 3h to obtain anacardic acid.
[0044] Example 2 Preparation of plasticizer:
[0045] S1: 100 g of deionized water, 25 g of urotropine, 10 g of tromethamine and 8 g of glacial acetic acid were added into the reactor in sequence, stirred, heated to 65°C, reacted for 2 h, cooled to room temperature to separate the layers, removed the water layer, washed with deionized water for 3 times (100 g of deionized water each time), and obtained the first generation polymer.
[0046] S2: Under nitrogen protection, 500g DMF, 50g first-generation polymer, and 150g anacardic acid were added to the reactor, stirred, and heated to 120°C. Then, 2g p-toluenesulfonic acid was added, refluxed for 6h, cooled to room temperature, and 100g saturated NaHCO was added. 3 The solution was distilled at 50 °C under reduced pressure for 2 h and dried in vacuo at 70 °C for 3 h to obtain intermediate 1.
[0047] S3: 500 g DMSO, 60 g intermediate 1, 150 g acetic anhydride and 2 g p-toluenesulfonic acid were added into the reactor in sequence, stirred, heated to 130°C, reacted for 8 h, distilled under reduced pressure at 70°C for 1 h, and vacuum dried at 90°C for 1 h to obtain intermediate 2.
[0048] S4: 500g DMF, 50g intermediate 2 and 5g strong acid cation exchange resin were added into the reactor, stirred and heated to 60°C; then 120g formic acid and 30g 30wt% H 2 O 2 Mix well and slowly add formic acid and H 2 O 2 The mixed solution was added dropwise for 5 minutes and reacted for 8 hours. After the reaction, deionized water was added for washing three times (150 g of deionized water was used each time), and the mixture was distilled at 60°C under reduced pressure for 3 hours to obtain intermediate 3.
[0049] S5: Add 1000g of tetrahydrofuran, 50g of intermediate 3, 200g of acetic anhydride and 2g of strong acid cation exchange resin into the reactor, stir, heat to 120°C, react for 8h, add deionized water for washing three times (150g of deionized water each time) after the reaction, distill at 70°C under reduced pressure for 40min, and vacuum dry at 60°C for 3h to obtain a plasticizer with a number average molecular weight of 12640.
[0050] Example 3 Preparation of plasticizer:
[0051] S1: 100 g of deionized water, 25 g of urotropine, 11 g of tromethamine and 9 g of glacial acetic acid were added into the reactor in sequence, stirred, heated to 70°C, reacted for 1.5 h, cooled to room temperature to separate the layers, removed the water layer, washed with deionized water for 3 times (100 g of deionized water each time), and obtained the first generation polymer.
[0052] S2: Under nitrogen protection, 500 g DMF, 75 g first-generation polymer, and 200 g anacardic acid were added to the reactor, stirred, and heated to 125 °C. Then, 3.5 g p-toluenesulfonic acid was added, refluxed for 5 h, cooled to room temperature, and 150 g saturated NaHCO was added. 3 The solution was distilled at 60 °C under reduced pressure for 1.5 h and dried under vacuum at 80 °C for 2 h to obtain intermediate 1.
[0053] S3: 500 g DMSO, 70 g intermediate 1, 180 g acetic anhydride and 3 g p-toluenesulfonic acid were added into the reactor in sequence, stirred, heated to 140°C, reacted for 7 h, distilled under reduced pressure at 60°C for 1.5 h, and vacuum dried at 80°C for 2 h to obtain intermediate 2.
[0054] S4: 500g DMF, 65g intermediate 2 and 8g strong acid cation exchange resin were added to the reactor, stirred, and heated to 70°C; then 140g formic acid and 35g 30wt% H 2 O 2 Mix well and slowly add formic acid and H 2 O 2 The mixed solution was added dropwise for 5 minutes and reacted for 7 hours. After the reaction, deionized water was added for washing three times (150 g of deionized water was used each time), and the mixture was distilled at 70°C under reduced pressure for 2 hours to obtain intermediate 3.
[0055] S5: Add 1000g of tetrahydrofuran, 80g of intermediate 3, 300g of acetic anhydride and 3g of strong acid cation exchange resin into the reactor, stir, heat to 130°C, react for 7h, add deionized water for washing three times (180g of deionized water each time) after the reaction, distill at 60°C under reduced pressure for 1h, and vacuum dry at 70°C for 2h to obtain a plasticizer with a number average molecular weight of 15470.
[0056] Example 4 Preparation of plasticizer:
[0057] S1: 100 g of deionized water, 25 g of urotropine, 12 g of tromethamine and 10 g of glacial acetic acid were added into the reactor in sequence, stirred, heated to 75°C, reacted for 1 h, cooled to room temperature to separate the layers, removed the water layer, washed with deionized water for 3 times (100 g of deionized water each time), to obtain a first-generation polymer.
[0058] S2: Under nitrogen protection, 500 g DMF, 100 g first-generation polymer, and 250 g anacardic acid were added to the reactor, stirred, and heated to 130 °C. Then, 5 g p-toluenesulfonic acid was added, refluxed for 4 h, cooled to room temperature, and 200 g saturated NaHCO was added. 3 The solution was distilled under reduced pressure at 70 °C for 1 h and dried under vacuum at 90 °C for 1 h to obtain intermediate 1.
[0059] S3: 500 g DMSO, 80 g intermediate 1, 200 g acetic anhydride and 4 g p-toluenesulfonic acid were added into the reactor in sequence, stirred, heated to 150°C, reacted for 6 h, distilled under reduced pressure at 50°C for 2 h, and vacuum dried at 70°C for 3 h to obtain intermediate 2.
[0060] S4: 500g DMF, 80g intermediate 2 and 10g strong acid cation exchange resin were added to the reactor, stirred, and heated to 80°C; then 160g formic acid and 40g 30wt% H 2 O 2 Mix well and slowly add formic acid and H 2 O 2 The mixed solution was added dropwise for 5 minutes and reacted for 6 hours. After the reaction, deionized water was added for washing three times (150 g of deionized water was used each time), and the mixture was distilled at 80°C under reduced pressure for 1 hour to obtain intermediate 3.
[0061] S5: Add 1000g of tetrahydrofuran, 100g of intermediate 3, 350g of acetic anhydride and 3g of strong acid cation exchange resin into a reactor, stir, heat to 140°C, react for 6h, add deionized water for washing three times after the reaction (200g of deionized water is used each time), distill at 50°C under reduced pressure for 2h, and vacuum dry at 80°C for 1h to obtain a plasticizer with a number average molecular weight of 17230.
[0062] Example 5 Preparation of PVC / SBS modified material:
[0063] S1: weigh PVC: 800g, SBS: 200g, plasticizer (prepared in Example 2): 30g, flame retardant (tributyl phosphate): 20g, antioxidant (N-phenyl-α-aniline): 50g, stabilizer (JX-181 organic tin heat stabilizer): 20g, lubricant (stearic acid): 30g;
[0064] S2: Add all components into a high-speed mixer and mix them. The mixing temperature is 110°C, the mixing speed is 200r / min, and the mixing time is 20min. Then the mixture is introduced into a twin-screw extruder for extrusion granulation. The screw speed of the screw extruder is 20r / s. The conveying section temperature of the twin-screw extruder is 120°C, the melting section temperature is 160°C, the mixing rubber section temperature is 170°C, and the homogenizing section temperature is 145°C. After air cooling and screening, the PVC / SBS modified material is obtained.
[0065] Example 6 Preparation of PVC / SBS modified material:
[0066] S1: Weigh PVC: 900g, SBS: 300g, plasticizer (prepared in Example 3): 150g, flame retardant (tri(2-ethylhexyl) phosphate): 30g, antioxidant (N-phenyl-β-naphthylamine): 70g, stabilizer (JX-107 reverse ester tin heat stabilizer): 25g, lubricant (stearic acid): 40g;
[0067] S2: Add all components into a high-speed mixer and mix them. The mixing temperature is 120°C, the mixing speed is 250r / min, and the mixing time is 25min. Then the mixture is introduced into a twin-screw extruder for extrusion granulation. The screw speed of the screw extruder is 20r / s. The conveying section temperature of the twin-screw extruder is 120°C, the melting section temperature is 160°C, the mixing rubber section temperature is 170°C, and the homogenizing section temperature is 145°C. After air cooling and screening, the PVC / SBS modified material is obtained.
[0068] Example 7 Preparation of PVC / SBS modified material:
[0069] S1: Weigh PVC: 1000g, SBS: 400g, plasticizer (prepared in Example 4): 300g, flame retardant (tris(2-chloroethyl) phosphate): 40g, antioxidant (N-phenyl-N'-isopropyl-p-phenylenediamine): 80g, stabilizer (JT-101 antimony mercaptan heat stabilizer): 30g, lubricant (stearic acid): 50g;
[0070] S2: Add all components into a high-speed mixer and mix them at a mixing temperature of 130°C, a mixing speed of 300r / min, and a mixing time of 30min. Then, introduce the mixture into a twin-screw extruder for extrusion granulation. The screw speed of the screw extruder is 20r / s, the conveying section temperature of the twin-screw extruder is 120°C, the melting section temperature is 160°C, the mixing rubber section temperature is 170°C, and the homogenizing section temperature is 145°C. After air cooling and screening, the PVC / SBS modified material is obtained.
[0071] Comparative Example 1
[0072] A PVC / SBS modified material, the raw material composition and process are basically the same as those of Example 6, the difference being that no plasticizer is added to the component.
[0073] Comparative Example 2
[0074] A PVC / SBS modified material, the raw material composition and process are basically the same as those of Example 6, the difference being that the plasticizer is replaced by an equal weight of the intermediate 2 prepared in step S3 of Example 3.
[0075] Comparative Example 3
[0076] A PVC / SBS modified material, the raw material composition and process are basically the same as those of Example 6, the difference being that the plasticizer is replaced by an equal weight of di-2-ethylhexyl phthalate.
[0077] Comparative Example 4
[0078] A PVC / SBS modified material is prepared by the following raw materials and processes:
[0079] S1: Weigh PVC: 800g, SBS: 200g, plasticizer: 30g, flame retardant (tri(2-ethylhexyl) phosphate): 20g, antioxidant (N-phenyl-α-aniline): 50g, stabilizer (JX-181 organic tin heat stabilizer): 20g, lubricant (stearic acid): 30g;
[0080] S2: Add all components into a high-speed mixer and mix them. The mixing temperature is 110°C, the mixing speed is 200r / min, and the mixing time is 20min. Then the mixture is introduced into a twin-screw extruder for extrusion granulation. The screw speed of the screw extruder is 20r / s. The conveying section temperature of the twin-screw extruder is 120°C, the melting section temperature is 160°C, the mixing rubber section temperature is 170°C, and the homogenizing section temperature is 145°C. After air cooling and screening, the PVC / SBS modified material is obtained.
[0081] The plasticizer in this comparative example was prepared by the following method:
[0082] S1: 100 g of deionized water, 25 g of urotropine, 11 g of tromethamine and 9 g of glacial acetic acid were added into the reactor in sequence, stirred, heated to 70°C, reacted for 1.5 h, cooled to room temperature to separate the layers, removed the water layer, washed with deionized water for 3 times (100 g of deionized water each time), and obtained the first generation polymer.
[0083] S2: Under nitrogen protection, 500 g DMF, 75 g first-generation polymer, and 200 g anacardic acid were added to the reactor, stirred, and heated to 125 °C. Then, 3.5 g p-toluenesulfonic acid was added, refluxed for 5 h, cooled to room temperature, and 150 g saturated NaHCO was added. 3 The solution was distilled at 60 °C under reduced pressure for 1.5 h and dried under vacuum at 80 °C for 2 h to obtain intermediate 1.
[0084] S3: 500 g DMSO, 70 g intermediate 1, 180 g acetic anhydride and 3 g p-toluenesulfonic acid were added into the reactor in sequence, stirred, heated to 140°C, reacted for 7 h, distilled under reduced pressure at 60°C for 1.5 h, and vacuum dried at 80°C for 2 h to obtain intermediate 2.
[0085] S4: 500g DMF, 40g intermediate 2 and 2g strong acid cation exchange resin were added into the reactor, stirred and heated to 70°C; then 60g formic acid and 10g 30wt% H 2 O 2 Mix well and slowly add formic acid and H 2 O 2 The mixed solution was added dropwise for 5 minutes and reacted for 7 hours. After the reaction, deionized water was added for washing three times (150 g of deionized water was used each time), and the mixture was distilled at 70°C under reduced pressure for 2 hours to obtain intermediate 3.
[0086] S5: Add 100 g of tetrahydrofuran, 30 g of intermediate 3, 100 g of acetic anhydride and 3 g of strong acid cation exchange resin into a reactor, stir, heat to 130°C, react for 7 h, add deionized water for washing three times (180 g of deionized water each time) after the reaction, distill at 60°C under reduced pressure for 1 h, and vacuum dry at 70°C for 2 h to obtain a plasticizer with a number average molecular weight of 9970.
[0087] Comparative Example 5
[0088] The PVC / SBS material was prepared using the raw material composition and proportion of Example 4 of the Chinese invention patent with publication number CN109265866A and the following method.
[0089] PVC resin and silicone modified SBS were added to a high-speed mixer at a mixing temperature of 110°C, a mixing speed of 200 r / min, and a mixing time of 20 min. Other additives (refer to the raw materials of Example 4 of the Chinese invention patent with publication number CN109265866A) were then added and mixed. The mixture was then introduced into a twin-screw extruder for extrusion granulation. The screw speed of the screw extruder was 20 r / s, the conveying section temperature of the twin-screw extruder was 120°C, the melting section temperature was 160°C, the mixing rubber section temperature was 170°C, and the homogenizing section temperature was 145°C. The mixture was air-cooled and sieved to obtain a PVC / SBS modified material.
[0090] The brand of PVC used in Examples 5-7 and Comparative Examples 1-5 of the present application is SG-5, purchased from Shanghai Chlor-Alkali Chemical Co., Ltd.; the brand of SBS used is SBS-4230; the strong acid cation exchange resin used is a polymer of divinylbenzene and sodium vinylbenzene sulfonate, brand Amberlite® IMAC HP1110 resin, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0091] The PVC / SBS modified materials prepared in Examples 5-7 and Comparative Examples 1-5 were subjected to tensile strength, elongation at break, impact strength, limiting oxygen index and low-temperature brittleness tests.
[0092] The tensile strength and elongation at break were tested in accordance with GB / T1040.1-2018 at a tensile speed of 100 mm / min; the impact strength was tested in accordance with GB / T1843-2008; the limiting oxygen index was tested in accordance with ISO4589-2; the low-temperature brittleness was tested in accordance with GB / T15256-2014 using a type B strip specimen. The test results are shown in Table 1.
[0093] Table 1
[0094]
[0095] It can be seen from Examples 5, 6 and 7 in Table 1 that the PVC / SBS modified materials prepared by the present invention have a tensile strength greater than 36 MPa, an elongation at break greater than 390%, and a notched impact strength greater than 45 KJ / m 2 , with excellent tensile properties and impact resistance.
[0096] Comparative Example 1 is a comparative example without adding plasticizer. From the data in Table 1, it can be seen that its tensile strength is 23.8MPa, the elongation at break is 310.6%, and the notched impact strength is 30.2KJ / m 2 .
[0097] Comparative Example 2 is different from Example 6 in that the plasticizer is replaced by the intermediate 2 prepared in step S3 of Example 3. From the data in Table 1, it can be seen that the tensile strength is 25.6 MPa, the elongation at break is 333.5%, and the notched impact strength is 33.5 KJ / m 2 .
[0098] Comparative Example 3 is different from Example 6 in that the plasticizer is replaced with diisooctyl phthalate. From the data in Table 1, it can be seen that the tensile strength is 27.9 MPa, the elongation at break is 351.7%, and the notched impact strength is 36.9 KJ / m 2 .
[0099] The number average molecular weight of the plasticizer added in Comparative Example 5 is 9970. From the data in Table 1, it can be seen that its tensile strength is 31.5MPa, the elongation at break is 374.2%, and the notched impact strength is 41.4KJ / m 2 .
[0100] Comparative Example 6 is a PVC / SBS material prepared by the raw materials of Example 4 of the Chinese invention patent with publication number CN109265866A and the process of this application. It can be seen from the data in Table 1 that its tensile strength is 26.1MPa, the elongation at break is 338.0%, and the notched impact strength is 33.9KJ / m 2 .
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A PVC / SBS modified material, characterized in that: The invention comprises the following raw materials in parts by weight: PVC: 80-100 copies, SBS: 20-40 copies, Plasticizer: 3-30 parts, Flame retardant: 2-4 parts, Anti-aging agent: 5-8 parts, Stabilizer: 2-3 parts, Lubricant: 3-5 parts; The plasticizer is prepared by the following method: S1: Deionized water, hexamethylenetetramine, tromethamine, and glacial acetic acid were added to the reactor in sequence, stirred, heated to 65-75°C, reacted for 1-2 hours, cooled to room temperature, separated, the water layer was removed, and washed with deionized water for 3 times to obtain a first-generation polymer; S2: Under nitrogen protection, DMF, first-generation polymer, and anacardic acid were added to the reactor, stirred, and heated to 120-130°C, and then p-toluenesulfonic acid was added. The reaction was refluxed for 4-6 hours, cooled to room temperature, and saturated NaHCO3 solution was added. The intermediate 1 was obtained by vacuum distillation and vacuum drying. S3: DMSO, intermediate 1, acetic anhydride and p-toluenesulfonic acid are added to the reactor in sequence, stirred, heated to 130-150°C, reacted for 6-8h, and post-treated to obtain intermediate 2; S4: DMF, intermediate 2 and strong acid cation exchange resin are added into a reactor, stirred and heated to 60-80°C; then formic acid and 30wt% H2O2 are mixed evenly, and the mixed solution of formic acid and H2O2 is slowly added dropwise, and the reaction is continued for 6-8h after the addition, and then the intermediate 3 is obtained by post-treatment; S5: Add tetrahydrofuran, intermediate 3, acetic anhydride and strong acid cation exchange resin into a reactor, stir, heat to 120-140°C, react for 6-8h, and post-treat to obtain a plasticizer.
2. A PVC / SBS modified material according to claim 1, characterized in that: In the step S1, the mass ratio of deionized water, hexamethylenetetramine, tromethamine and glacial acetic acid is 10:2.5:(1.0-1.2):(0.8-1.0).
3. A PVC / SBS modified material according to claim 1, characterized in that: In the step S2, the mass ratio of DMF, first-generation polymer, anacardic acid and p-toluenesulfonic acid is 50:(5-10):(15-25):(0.2-0.5).
4. A PVC / SBS modified material according to claim 1, characterized in that: In the step S3, the mass ratio of DMSO, intermediate 1 and acetic anhydride is 50:(6-8):(15-20).
5. A PVC / SBS modified material according to claim 1, characterized in that: In the step S4, the feed mass ratio of DMF, intermediate 2, formic acid and strong acid cation exchange resin is 50:(5-8):(12-16):(0.5-1).
6. A PVC / SBS modified material according to claim 1, characterized in that: Said In step S5, the mass ratio of tetrahydrofuran, intermediate 3 and acetic anhydride is 100:(5-10):(20-35).
7. A PVC / SBS modified material according to claim 1, characterized in that: The flame retardant is one of tributyl phosphate, tri(2-ethylhexyl) phosphate, and tri(2-chloroethyl) phosphate; the antioxidant is one of N-phenyl-α-aniline, N-phenyl-β-naphthylamine, and N-phenyl-N'-isopropyl-p-phenylenediamine.
8. A PVC / SBS modified material according to claim 1, characterized in that: The stabilizer is a combination of one or more of JX-181 organic tin heat stabilizer, JX-107 reverse ester tin heat stabilizer, and JT-101 antimony mercaptan heat stabilizer.
9. A PVC / SBS modified material according to claim 1, characterized in that: The lubricant is stearic acid.
10. A method for preparing the PVC / SBS modified material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh by weight: PVC: 80-100 parts, SBS: 20-40 parts, plasticizer: 3-30 parts, flame retardant: 2-4 parts, antioxidant: 5-8 parts, stabilizer: 2-3 parts, lubricant: 3-5 parts; S2: Add all components into a high-speed mixer and mix them. Then, introduce the mixture into a twin-screw extruder for extrusion and granulation, and air-cool and sieve to obtain the PVC / SBS modified material.
Citation Information
Patent Citations
PVC cable material resistant to pigment transference
CN109265866A
PVC modified material for food and preparation method thereof
CN107698898A
Anti-tear flame-retardant cable and preparation method thereof
CN118206832A